Academia Română, Institutul de Istoria Artei "G. Oprescu" - Institutul de Istoria Artei (2009)
[Dt.:] Die Website des Kunsthistorischen Institutes in Bukarest benannt nach dem rumänischen Kunsthistoriker George Oprescu (1881-1969) bietet Informationen zur Geschichte des Institutes, zu Projekten, zu Veröffentlichungen, zur Bibliothek, etc. - [Engl.:] The Institute of History of Art in Bucharest was named after the Rumanian art historian George Oprescu (1881-1969). Its website provides information on the Institute's history, on projects, on publications, the library, etc.